The Status of Old English Dare Revisited - Gregersen, Sune (Studia Anglica Posnaniensia, 2017)
The development of dare in the history of English has played an important role in the literature on grammatical change and (de)grammaticalization. This paper aims to clarify two issues regarding the syntax and semantics of dare in earlier English: when it is first attested with to-infinitives, and to what extent it can be said to have been semantically ‘bleached’ in a number of Old English attestations. The conclusions are, firstly, that dare is not attested with to-infinitives in Old English (pace Tomaszewska 2014), and that a number of Middle English attestations that have been suggested in the literature are not convincing (pace Visser 1963–73; Beths 1999; Molencki 2005). Secondly, it is argued that the co-occurrence of dare and verbs like gedyrstlæcan ‘venture, be bold, presume’ in Old English is not an indication of semantic ‘bleaching’ of dare, and that the verb was not more ‘auxiliarized’ in Old English than it is today.